2018
DOI: 10.1007/s40194-018-0612-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing temperatures on the properties of a high-strength steel welded by FSW

Abstract: The need for weight reduction without compromising load-bearing capacity has driven the development of modern high-strength steels (HSS). The ability to take full advantage of these modern HSS is limited by their weldability. Friction stir welding (FSW) can join HSS at low peak temperatures, better preserving the properties of the base material. This work evaluates the influence of different FSW peak temperatures and cooling rates on the properties of a modern HSS. A HSS produced by a thermomechanically contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It can be seen in Figure 17 that the Ys, UTS, and E% of FSWed joints are enhanced over the BM by 65%, 33%, and 54%, and over the GTAW weldments by 21%, 41%, and 66%, respectively. This enhancement of the tensile properties is mainly ascribed to the main features of grain modification during the FSW process [ 53 ]. Ghadar et al [ 38 ] reported significant improvement of ultimate tensile strength and fracture strain for friction stir processed 3.5 mm 2205 DSS and ascribed this enhancement in tensile properties to the grain refining.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen in Figure 17 that the Ys, UTS, and E% of FSWed joints are enhanced over the BM by 65%, 33%, and 54%, and over the GTAW weldments by 21%, 41%, and 66%, respectively. This enhancement of the tensile properties is mainly ascribed to the main features of grain modification during the FSW process [ 53 ]. Ghadar et al [ 38 ] reported significant improvement of ultimate tensile strength and fracture strain for friction stir processed 3.5 mm 2205 DSS and ascribed this enhancement in tensile properties to the grain refining.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the application of a single pass advanced welding solutions to modern TMCP HSS with a minimum yield strength of 700 MPa, as demonstrated by Sorger et al [14,15] in the application of friction stir welding with faster welding speed conditions, or Górka et al [16] in the application of hybrid laser arc welding, the multi-pass fusion welding can induce excessive decrease of impact-toughness, eventually due to the intercritically reheated domains that are formed in the HAZ [17,18]. On this scope, Hu et al [19] observed that V-N micro-alloying improved the toughness of the ICCGHAZ (inter-critically reheated coarse grained heat affected zone) by decreasing the size of M/A (martensitic/austenitic) constituents and refining the ferrite forming on the prior austenite grain boundaries [19].…”
Section: Introductionmentioning
confidence: 99%
“…This result is confirmed with the hardness measurements shown in Figure 11a,b. This improvement in UTS and YS is mainly attributed to the developed microstructure modification through the FSW [47]. Ghadar et al [48] concluded that friction stir processing 2205 DSS promotes significant UTS and ductility enhancement compared to as-received material.…”
Section: Hardness and Tensile Propertiesmentioning
confidence: 99%